Analysis of the article weight product method and weight sum method on decision support systems: Systematic Review - Khairina Eka Setyaputri; Wicaksono Yuli Sulistyo (Institute of Computer Science (IOCS), 2023)
A decision support system (DSS) is a problem processing system between two components consisting of one or more general problem manipulation capabilities required in decision making. Decision making is basically a form of selecting from various alternative actions. DSS has various methods of solving problems. In this literature review, research focuses on the use of the Weighted Product (WP) and Weighted Sum Model (WSM) methods in decision-making systems. Systematic reviews are limited to research in the form of articles that have been reviewed and published in journals. Eight articles were obtained to be reviewed in this study. The results of the literature show that the two methods have different decision outcomes. Another result is that the WP method has better decision outcomes than WSM in solving problems